Preparation And Study Of Some Electrical Properties Of Mn-Ni Fe2O4 - Saadon, Abbas Kareem (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this study, Mn-Ni Ferrite was prepared by using two composites of manganese ferrite ( MnFe2o4 )  and Nicle Ferrite ( NiFe2O4) tested by X-Ray diffraction (XRD) method. The dielectric constant (ðœ€Ì…) and the dielectric loss tangent (ð‘¡ð‘Žð‘› ð›¿) were studied for the ferrite system prepared at different frequencies (100, 200â€¦ and 5000 kHz). It was found that the values of (ðœ€Ì…) and (ð‘¡ð‘Žð‘› ð›¿) decrease with the  increase of frequencies.